Pendalaman Konsep Matematika bagi Para Guru Sekolah Dasar - Uskono, Irmina Veronika; Leton, Samuel Igo; Lakapu, Meryani; Djong, Kristoforus Djawa; Jagom, Yohanes Ovaritus; Dosinaneg, Wilfridus Beda Nuba (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
Mastery of mathematical concepts and skills in solving mathematical problems are basic abilities that must be possessed by mathematics teachers. Teachers must be able to provide strategies in producing solutions related to problems that become problems among students so that they are able to participate in learning activities properly. SD St. Angela Atambua is one of the education providers that wants to realize the goals of education. But in reality there are still many obstacles faced by St. Angela Elementary School teachers regarding the right strategies in overcoming students' problems, especially in concept mastery. Therefore, the service team together with the teachers of SD St. Angela Atambua tried to solve the problems of students by conducting training and mentoring in order to build a new mindset in solving every problem related to mathematics learning. The expected goal is that teachers are able to overcome the problems faced by students. The method used in this service is training and mentoring. Some of the positive things obtained from the implementation of this service include; 1) teachers are very enthusiastic in participating in activities because they get new information. 2) the service team provided assistance according to the problems experienced by the partners. 3). teachers are able to implement the concepts that have been obtained so that they can develop ideas and creativity by utilizing existing learning media as a form of solution to the problems experienced. With this math concept planting training, it is able to answer the challenges faced by partners so that students can take part in learning more enthusiastically and enthusiastically and can increase interest, motivation to learn, especially understanding of mathematical concepts to be better.